UPAYA PEMBINAAN PRANIKAH GUNA MEWUJUDKAN TUJUAN PERKAWINAN OLEH KANTOR URUSAN AGAMA KOTA UTARA KOTA GORONTALO - IDRUS, NAZLA ABD AL; THALIB, MUTIA CHERAWATY; MOHA, MOHAMAD RIVALDI (GANEC SWARA, 2024)
Divorce is still the path chosen by most people to end the marital ties that have existed. The high divorce rate needs to be a common concern to reduce and prevent this. Premarital formation is an effort to prevent divorce and realize the goals of marriage in Law Number 1 of 1974 concerning Marriage. This research aims to determine pre-marital coaching efforts to achieve marriage goals by the North City KUA, Gorontalo City. This research is classified as empirical legal research with a comparative approach. Data sources consist of primary data and secondary data obtained through interviews and literature studies which are then analyzed descriptively qualitatively. The research results show that efforts to provide premarital guidance to achieve marriage goals by the North City KUA of Gorontalo City have not been optimal because even though the North City KUA has provided active premarital guidance, the divorce rate is still there, although the number has decreased.